Produção de mudas de Sapindus saponaria L. - SILVA, Sheylla Cristiny Alves da (2015)
The Sapindus saponaria L. commonly known as soap belongs to the Sapindaceae family, it is a forest that has ornamental and medicinal purposes, and is used in folk medicine for a long time. The objective was to evaluate the effect of different levels of shading and depth in the production of seedlings of S. saponaria. After removal of seed from the fruit, they were placed in sulfuric acid 98% for 60 minutes, and dormancy breaking method, then seeded in polypropylene bags containing as soil substrate and goat manure in the proportion of 4: 1 in the depths of one and two cm. The bags were placed at 0, 50 and 75% shading. The experiment was conducted in a randomized block in a factorial 3 x 2 (shading x depth), with four replications. The following variables were evaluated: percentage, first count and emergence speed index, plant height, stem diameter, number of leaves, chlorophyll content, root volume, leaf area, length and dry mass of roots and shoots. Data were subjected to analysis of variance and means compared by Tukey test at 5% probability. The production of S. saponaria L. seedlings can be performed under shading (50 and 75%) with seeding at 1 and 2 cm deep. As well as the shading of 0% at a depth of 2cm.